Use of video laryngoscope for tracheal intubation in patient with oral cavity mass: case report - Cangiani,Luis Henrique (2020)
Abstract Background and objectives When planning the management of a predicted difficult airway, it is important to determine which strategy will be followed. Video laryngoscopy is a major option in scenarios with factors suggesting difficult airway access. It is also indicated in rescue situations, when there is tracheal intubation failure with direct laryngoscopy. The objective of the present report was to show the efficacy of using the video laryngoscope as the first device for a patient with a large tumor that occupied almost the entire anterior portion of the oral cavity. Case report An 85 year-old male patient, 162 cm, 70 kg, ASA Physical Status II, Mallampati IV classification, was scheduled for resection of an angiosarcoma located in the right maxillary sinus that invaded much of the hard palate and the upper portion of the oropharynx. He was conscious and oriented, with normal blood pressure, heart and respiratory rates and, despite the large tumor in the oral cavity, he showed no signs of respiratory failure or airway obstruction. After intravenous cannulation and monitoring, sedation was performed with 1 mg of intravenous midazolam, and a nasal cannula was placed to provide oxygen, with a flow of 2 L min−1. Then, the target-controlled infusion of remifentanil with an effect site concentration of 2 ng mL−1 was initiated, according to Minto's pharmacokinetic model. Ventilation was maintained spontaneously during airway handling. A trans-cricothyroid block was performed, with 8 mL of 1% lidocaine solution injected into the tracheal lumen. Slight bleeding did not prevent the use of an optical method for performing tracheal intubation. The entire oral cavity was sprayed with 1% lidocaine. The McGraph video laryngoscope with the difficult intubation blade was used, and an armored tube with a guide wire inside was used for tracheal intubation, performed on the first attempt with appropriate glottis visualization. Conclusion The video laryngoscope occupies a prominent position in cases in which access to the airway is difficult. In the present case it was useful. It can be used as first choice or as a rescue technique. The video laryngoscope is an appropriate alternative and should be available for facing the ever-challenging difficult airway patient.